Birds and Habitat Characteristics in a Very Humid Tropical Forest in the Costa Rican Caribbean - Maglianesi, María Alejandra (2007)
Field work was conducted since late July until late December 2002 near Tortuguero, northern Caribbean coast in Costa Rica, Limon Province. Bird community was examined in five sites, two disturbed and three undisturbed wet lowland forest, in order to suggest appropriate management strategies. Species richness and relative abundance were determined by combining mist-netting and area search count data. Number of fruits available to birds was measured in four sites during the same period that birds were netted and observed. I recorded a total of 128 species of birds, migrant species were more common in disturbed habitats and resident species avoid these habitats. Sites with more fruit abundance were the same that sites with more frugivorous species.